## Fully nonlinear ellipticity and conformal invariancy

Let $\mathcal{S}^{n\times n}$ be the space of symmetric $n\times n$ matrices and $\mathcal{O}(n)$ is the orthogonal matrices. Suppose $U\subset \mathcal{S}^{n\times n}$ satisfies

$\displaystyle O^{-1}UO=U$, $\forall\, O\in \mathcal{O}(n)$

Let $F\in C^1(U)$ satisfy

$\displaystyle F(O^{-1}MO)=F(M)$, $\forall\, M\in U$, and $O\in \mathcal{O}(n)\quad$      (1)

The fully nonlinear equation $F(D^2u)=\psi$ is called elliptic in $U$ if

$(F_{ij})(D^2u)>0$ for any $D^2u\in U\quad$      (2).

From (1), we know there exists $f\in C^1$ such that $F(M)=f(\lambda_1,\lambda_2,\cdots,\lambda_n)$, where $\lambda_1,\lambda_2,\cdots,\lambda_n$ are the eigenvalues of $M$. And $f$ must be symmetric.

$\mathbf{Problem:}$ $F$ is elliptic is equivalent to $\displaystyle \frac{\partial f}{\partial \lambda_i}>0$, $\forall\, i$

$\mathbf{Proof:}$ Firstly, let us assume $F$ is elliptic, i.e. $F_{ij}(M)>0$, $\forall M\in U$.

Then in particular choose $M=\Lambda=diag\{\lambda_1,\lambda_2,\cdots,\lambda_n\}\subset U$,

$f(\lambda_1,\lambda_2,\cdots,\lambda_n)=F(\Lambda)$

Then                                             $\displaystyle \frac{\partial f}{\partial \lambda_i}=F_{ii}(\Lambda)>0$

Secondly, assume $\displaystyle \frac{\partial f}{\partial \lambda_i}>0$, $\forall\, i$.

$\forall\, M\in U$, there exists $O\in \mathcal{O}(n)$ such that $M=O\Lambda O^{-1}$, here we denote $O=(O_{ij}), O^{-1}=(O^{ij})$.

Then $F(M)=F(O\Lambda O^{-1})=F((O_{ik}\lambda_{k}O^{kj}))=f(\lambda_1,\lambda_2,\cdots,\lambda_n)$

Differentiating (1), we get       $\displaystyle \sum_{i,j}O^{ik}F_{ij}(O^{-1}MO)O_{lj}=F_{kl}(M)$

That is                       $\displaystyle \sum_{i,j}O^{ik}F_{ij}(\Lambda)O_{lj}=F_{kl}(M)\quad (3)$

Since $F(\Lambda)=f(\lambda_1,\lambda_2,\cdots,\lambda_n)$, then $\displaystyle F_{ii}(\Lambda)=\frac{\partial f}{\partial \lambda_1}$, $\forall\, i>0$

For $F_{ij}(\Lambda)$, when $i\neq j$, by definition and use the fact that $\boldsymbol{F_{ij}=F_{ji}}$(possible to remove?)

$\displaystyle 2F_{ij}(\Lambda)=\lim\limits_{a \to 0}\frac{F(\Lambda+aE_{ij})-F(\Lambda)}{a}$

here $E_{ij}$ is symmertric and has entries which are 0 except at $(i,j)$-th and $(j,i)$-th positions are 1.

$\displaystyle \Lambda+tE_{ij}$ has eigenvalue $\lambda_k$ with $k\neq i,j$ and $\displaystyle \frac{\lambda_i+\lambda_j+\sqrt{(\lambda_i-\lambda_j)^2+4a^2}}{2}$, $\displaystyle \frac{\lambda_i+\lambda_j-\sqrt{(\lambda_i-\lambda_j)^2+4a^2}}{2}$.

So $\displaystyle F_{ij}(\Lambda)=\lim\limits_{a \to 0}\frac{F(\Lambda+aE_{ij})-F(\Lambda)}{2a}=\lim\limits_{a \to 0}\frac{f(\lambda_1,\lambda_2,\cdots,\lambda_n)-f(\lambda_1,\lambda_2,\cdots,\lambda_n)}{2a}$

$\displaystyle =\lim\limits_{a \to 0}\frac{f(\lambda_1,\cdots, \frac{\lambda_i+\lambda_j+\sqrt{(\lambda_i-\lambda_j)^2+4a^2}}{2},\cdots,\frac{\lambda_i+\lambda_j-\sqrt{(\lambda_i-\lambda_j)^2+4a^2}}{2},\cdots,\lambda_n)-f(\lambda_1,\lambda_2,\cdots,\lambda_n)}{2a}\quad (4)$

• If $\lambda_i=\lambda_j=\mu$, then (4) becomes

$\displaystyle F_{ij}(\Lambda)=\lim\limits_{a \to 0}\frac{f(\lambda_1,\cdots, \mu+a,\cdots,\mu-a,\cdots,\lambda_n)-f(\lambda_1,\lambda_2,\cdots,\lambda_n)}{2a}$

$\displaystyle =\frac{1}{2}\left(\frac{\partial f}{\partial \lambda_i}(\lambda_1,\lambda_2,\cdots,\lambda_n)-\frac{\partial f}{\partial \lambda_j}(\lambda_1,\lambda_2,\cdots,\lambda_n)\right)=0,$

because $f$ is symmetric and $\lambda_i=\lambda_j$.

• If $\lambda _i\neq \lambda_j$, (4) becomes

$\displaystyle F_{ij}(\Lambda)=\frac{\partial f}{\partial \lambda_i}(\lambda_1,\lambda_2,\cdots,\lambda_n)\lim\limits_{a\to 0}\frac{\lambda_j-\lambda_i+\sqrt{(\lambda_i-\lambda_j)^2+4a^2}}{2a}+\frac{\partial f}{\partial \lambda_j}(\lambda_1,\lambda_2,\cdots,\lambda_n)\lim\limits_{a\to 0}\frac{\lambda_i-\lambda_j-\sqrt{(\lambda_i-\lambda_j)^2+4a^2}}{2a}$

$\quad =0$

Combing the above results, we get $\displaystyle (F_{ij}(\Lambda))=diag\left\{\frac{\partial f}{\partial \lambda_1},\frac{\partial f}{\partial \lambda_2}\cdots,\frac{\partial f}{\partial \lambda_n}\right\}$.

Applying $(F_{ij}(\Lambda))$ to (3), it becomes $\displaystyle \sum_{i}O^{ik}\frac{\partial f}{\partial \lambda_i}(\lambda_1,\lambda_2,\cdots,\lambda_n)O_{li}=F_{kl}(M)$

This means $\displaystyle O\left(diag\left\{\frac{\partial f}{\partial \lambda_1},\frac{\partial f}{\partial \lambda_2}\cdots,\frac{\partial f}{\partial \lambda_n}\right\}\right)O^{-1}=(F_{kl}(M))^T$.

$(\displaystyle F_{kl}(M))$ is a positive definite matrix because  $\displaystyle \frac{\partial f}{\partial \lambda_i}>0$, $\forall\, i$.

$\text{Q.E.D}\hfill \square$

$\mathbf{Remark:}$